(untitled) (Bangladesh Journal of Livestock Research, 2021)
Isolation and identification of probiotic bacteria are the prerequisites for their safer use in the food and feed industry. The objectives of the present study were the isolation of probiotic bacteria from the selective gastrointestinal tract of poultry obtained from Khulna and Barisal Divisions, and their identification based on bacterial morphological characterization and biochemical property analysis. Ten potential native probiotics were isolated from the poultry gastrointestinal tract and assayed for their morphological, physiological and biochemical properties. It was observed that, all the isolates were rod-shaped, gram-positive, endospore-negative, catalase-negative, non-motile and were able to ferment particular sugars which are an indicator for typical probiotic bacteria. The sugar fermentation pattern, ability to survive and growth in inhibitory substances like 1-4% NaCl, 0.3% bile salt as well as their ability to grow in different temperatures and pH levels ensured the presumptive identification of the lactic acid bacteria. All the ten isolates exhibited a clear zone of inhibition when they were grown with five enteric pathogens which are indicative of their antimicrobial activity. Ten isolates were assayed for their susceptibility to eight antibiotics using the disc diffusion method. All the isolates were resistant to tetracycline and nalidixic acid. Further research regarding molecular characterization and identification of specific genes using different technologies may open the door to utilize these isolates in different probiotic-based inventions. Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 39-54